Diversity of Coliphages and Coliforms in Horse Feces Reveals a Complex Pattern of Ecological Interactions - Golomidova, Alla; Kulikov, Eugene; Isaeva, Alina; Manykin, Anatoly; Letarov, Andrey (Applied and Environmental Microbiology, 2007)
The diversity of coliphages and indigenous coliform strains (ICSs) simultaneously present in horse feces was investigated by culture-based and molecular methods. The richness of coliforms (as estimated by the Chao1 method) is about 1,000 individual ICSs distinguishable by genomic fingerprinting present in a single sample of feces. This unexpectedly high value indicates that some factor limits the competition of coliform bacteria in the horse gut microbial system. In contrast, the diversity of phages active against any selected ICS is generally limited to one to three viral genotypes present in the sample. The sensitivities of different ICSs to simultaneously present coliphages overlap only slightly; the phages isolated from the same sample on different ICSs are usually unrelated. As a result, the titers of phages in fecal extract as determined for different Escherichia coli strains and ICSs may differ by several orders of magnitude. Summarizing all the data, we propose that coliphage infection may provide a selection pressure that maintains the high level of coliform diversity, restricting the possibility of a few best competitors outgrowing other ICSs. We also observed high-magnitude temporal variations of coliphage titers as determined using an E. coli C600 test culture in the same animal during a 16-day period of monitoring. No correlation with total coliform count was observed. These results are in good agreement with our hypothesis.